(untitled) (Revista Española de Derecho Internacional, 2007)
Nowadays we can say that the Spanish conflict of law system is changing because of the new immigration movement of people. The new private international situations that are connected with the immigration have had also a influence into the function of Private International Law, that is now the integration of people in the State of residence and in the State of origin, because people don’t loose the links with their State of origin during all the life. These new situations demands also new regulation methods for granting the enforcement of the relations creates in the State of residence in the origin State. For this reason the enforcement of decisions is not only part of the content of Private International Law, but also a new method for de regulation of the private international situations connected with the immigration. This new «enforcement method» permits to the authorities the constitution of legal situations that could be recognised in the State of origin and the enforcement in Spain of the relations creates in this last State without making a control of the law applied by the origin authorities.